SISTEM INFORMASI PENYALURAN OBAT DIPT. KIMIA FARMA (PERSERO) BERBASIS WEB - Johan Dwi Cahyo; K. Ghazali; Suzan Agustri (Jurnal Informatika Global)
PT. Kimia Farma(Persero) is a trading and distributor company which trusted to distribute various drugs to drugstores in South Sumatera region. In this company still exist some weaknesses that must be polished up, one of them is in the drug distribution, if the drugstores want to order drugs, they have to call the administration section first, then the administration section will do drug stock checking to the warehouse if the ordered drug stock is still exist or not and the warehouse section will notify to the administration section, then the administration section will call back drugstore to notify about the drug stock. If there is supply of drugs in the storage, the administration section will notify the drugstore party that the ordered drug is exist, so that the warehouse section will prepare the drug, after the drug order is prepared, will send the orders through transportation. The method used is Waterfall which consists of analysis, design, code, testing and maintenance. The system design uses Unified Modeling Language which consists of Use Case Diagram, Sequence Diagram, Activity Diagram, Class Diagram and File Specification. This application is built using PHP language programming and Xampp as the base of data. Keywords:Information System, Distribution, Drug, Waterfall,Web